INTERAKSI KAWASAN RUKO TERHADAP LINGKUNGAN SEKITARNYA STUDI KASUS PADA DUA KAWASAN RUKO YANG TERLETAK DI PUSAT KOTA KENDARI SULAWESI TENGGARA - , Rizky Noval W ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Efficient use of land is one of the answers to overcome land constraints due to the increasing number of residents. Shophouse is a building that has multiple functions for trading and a place for living, because of its efficiency, the current face of Indonesian cities are decorate by many shophouses. Kendari is located in the southeast of Sulawesi island, and the capital city where of Southeast Sulawesi, is also facing fews phenomena. the number of shophouses in Kendari Increase by year significntly. The existence of the shophouses is very much expected to be one of the causes of many issues in environmental, such us unhygiene, flooding, congestion and others that occur in several places in the Kendari city. This study aims to examine the interactions between the shophouses area and its surrounding through the conditions of its environment, economy, and social, as well as to identify the factors that influence the occurrence of these interactions. This research uses a case study method. It is to expect that from the experiences that occured in Kendari city, this research can also enrich the concept of shophouses development cities with urban life. Based on these research, it was found the interaction of shophouses area and its surrounding, as well as the factors that influence the interactions. These factors can be as learning experience for other areas in other regions to manage the development of shophouses.